2019
DOI: 10.2478/gp-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Bangla version of the Kessler Psychological Distress Scale (K6)

Abstract: ObjectiveThe 6 item Kessler Psychological Distress Scale (K6) is a screening tool for psychological distress with robust psychometric properties; however, information is lacking on such properties of the scale on its Bangla version. The aim of this study was to evaluate the psychometric properties of the Bangla version of the K6 scale in young people.MethodA self-administered questionnaire survey was conducted between August 2017 and April 2018 among 718 students aged 13-24 years (45% females) from Dhaka, Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 34 , 35 The Cronbach’s alpha in several countries (Vietnamese [0.86], Arabic [0.81], Bangladeshi [0.87–0.88], Chinese [0.84], and Persian [0.87] versions) was similar. 37 , 38 , 46 , 60 , 61 By contrast, Cronbach’s alpha increases with the number of items on the scale. 43 In fact, previous studies have shown that the Cronbach’s alpha of the K10 (Japanese version = 0.91, Persian version = 0.92) is higher than that of the K6 (Japanese version = 0.85, Persian version = 0.87).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 34 , 35 The Cronbach’s alpha in several countries (Vietnamese [0.86], Arabic [0.81], Bangladeshi [0.87–0.88], Chinese [0.84], and Persian [0.87] versions) was similar. 37 , 38 , 46 , 60 , 61 By contrast, Cronbach’s alpha increases with the number of items on the scale. 43 In fact, previous studies have shown that the Cronbach’s alpha of the K10 (Japanese version = 0.91, Persian version = 0.92) is higher than that of the K6 (Japanese version = 0.85, Persian version = 0.87).…”
Section: Discussionmentioning
confidence: 94%
“…The ICC of the Bangladesh version is 0.80, which is similar to our results. 60 The test–retest reliability of the K6 scores in other countries, including China and Iran, are also identified. 46 , 61 , 62 However, the Pearson or Spearman correlation coefficient was used as a measure of test–retest reliability in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized four primary scales to capture an array of psychological, environmental, and social factors. The Kessler Psychological Distress Scale (K10) was previously adapted to Bengali following a comprehensive translation process, consistent with existing research affirming its validity and reliability in the Bengali-speaking population ( Islam, 2019 ; Kessler et al, 2002 ; Khan et al, 2019 ; TMHC, 2012 ; Uddin et al, 2018 ). Alongside the K10, the Bengali version of the Depression Anxiety Stress Scale (DASS-21) was also administered, which has been validated for use in Bangladesh ( Sadiq et al, 2019 ; Sarkar et al, 2018 ).A custom Environmental Stressor Scale (ESS) was developed for this study, modeled on previous works to measure environmental stressors specifically related to sea-level rise ( Hahn, Riederer, & Foster, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients’ psychological distress was assessed using Kessler Psychological Distress Scale (K‐10). This scale has five Likert's response, ranging from none of the time to all of the time 23 . Patients who responded none of the time to all items in the Likert's scales were said to have no psychological distress.…”
Section: Methodsmentioning
confidence: 99%